OIL POLLUTION DETECTION USING RESISTIVITY SOUNDING - Shevnin V.; Delgado-Rodríguez O.; Mousatov A.; Nakamura-Labastida E.; Mejía-Aguilar A. (My University, 2003)
Resistivity sounding technology is applied to the characterization of oil polluted areas. It includes the analysis of the model of oil pollution as a low resistivity zone, the field study technique, advanced data processing, petrophysical simulation and data interpretation. Oil pollution is widespread and arises at all stages of the petroleum industry: extraction, transportation, refining and distribution. Under the influence of biodegradation, oil pollution in the ground changes the resistivity of the groundwater and the surrounding rocks, exhibiting as a zone of low resistivity. Resistivity sounding can estimate its position in plan and with depth, lithology, pollution sources, possible migration paths and contamination grade. Resistivity soundings are performed as electrical resistivity tomography (ERT), which has high space resolution and low distortion caused by near-surface inhomogeneities (geological noise). For the separation of contaminated and non-contaminated areas, a petrophysical simulation is used for calculation of rock resistivity based on underground water resistivity or salinity.
Keywords: resistivity sounding; oil pollution; biodegradation; geological noise; petrophysical simulation